Portfolio Performance Evaluation: Old Issues and New Insights - Grinblatt, Mark; Titman, Sheridan (Review of Financial Studies, 1989)
[This article presents a model that provides insights about various measures of portfolio performance. The model explores several criticisms of these measures. These include the problem of identifying an appropriate benchmark portfolio, the possibility of overestimating risk because of market-timing ability, and the failure of informed investors to earn positive risk-adjusted returns because of increasing risk aversion. The article argues that these need not be serious impediments to performance evaluation.]